A comprehensive evaluation of the endocrine-disrupting effects of emerging organophosphate esters - Quan Zhang; Liuqing Yang; Huiyun Wang; Chengwang Wu; Rui Cao; Meirong Zhao; Guanyong Su; Cui Wang (Environment International, 2024)
The ubiquitous presence of organophosphate esters (OPEs) in the environment has prompted growing concerns about their potential health risks, particularly their endocrine-disrupting effects. This study comprehensively evaluated the endocrine-disrupting properties of six emerging OPEs: five aryl-OPEs (2-ethylhexyl diphenyl phosphate (EHDPP), tris (2-biphenylyl) phosphate (TBPP), resorcinol bis (diphenyl phosphate) (RDP), 4-hydroxyphenyl diphenyl phosphate (para-OH-TPHP), and 3-hydroxyphenyl diphenyl phosphate (meta-OH-TPHP) and one alkyl-OPE, triallyl phosphate (TAP). Our findings revealed that all tested aryl-OPEs exhibited antagonistic effects on one or more hormone receptors. Importantly, para-OH-TPHP demonstrated the most potent antagonistic activity, inhibiting estrogen receptor α (ERα), thyroid hormone receptor β (TRβ), glucocorticoid receptor (GR), and mineralocorticoid receptor (MR) with the concentration of test compounds showing 20 % relative inhibitory concentration (RIC20) value below 10−6 mol/L (M). RDP antagonized ERα and cortical receptors (GR and MR), TBPP affected TRβ and GR, while EHDPP and meta-OH-TPHP targeted MR. Regarding steroidogenesis, para-OH-TPHP significantly inhibited genes for estrogen (cyp19) and cortisol synthesis (cyp11b2), and along with meta-OH-TPHP, EHDPP, TAP, and RDP downregulated cyp11a1, a rate-limiting enzyme in hormone synthesis. All compounds caused malformations and swimming abnormalities in zebrafish embryos/larvae at concentrations of 10−7 M or higher, with para-OH-TPHP showing nearly 50 % peak induction. Furthermore, the six compounds tested influenced genes associated with the hypothalamic-pituitary–gonadal (HPG) axis in both zebrafish larvae and adult female zebrafish, in addition to affecting the reproductive behavior of zebrafish. A weighted scoring system was employed to rank the endocrine-disrupting potency of the OPEs, with para-OH-TPHP exhibiting the highest risk, followed by EHDPP, RDP, TBPP, meta-OH-TPHP, and TAP. Collectively, our results highlight the significant endocrine-disrupting effects of emerging OPEs, underscoring the urgent need for further research to assess their potential health implications.